1987
DOI: 10.1111/j.1439-0485.1987.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Polychaete Vertical Zonation along a Littoral Cliff in the Western Méditerranean

Abstract: . Along the vertical cliff of Romito (Leghorn, Italy) 97 polychaete species were found from 0 to 6 m depth. Three depth related communities could be identified by trends in structural parameters (abundance, number of species, and diversity), by changes in species composition, and by the distribution of ecological and trophic groups. Such a zonation is consistent with the principal models proposed for the Méditerranean and seems mainly related to algal conditioning of the substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
6

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 7 publications
(1 reference statement)
1
40
1
6
Order By: Relevance
“…I tested the hypothesis that syllid distribution related significantly to the abundance of dominant, habitat-forming macrobenthic species, such as the articulated coralline alga Amphiroa sp., which was dominant at 1.5 m depth. Unexpectedly, I found no significant relationship between this alga and syllid distribution, in contrast to observations elsewhere (Abbiati et al 1987, Serrano et al 2006. Geography and habitat dissimilarity might be at the base of the differences between the present study and that of Serrano et al (2006), who concluded that variation in abundance of habitat-forming taxa is one of the most important factors influencing the distribution of Syllidae along the Atlantic Iberian coast.…”
Section: Association With Dominant Macrobenthic Speciescontrasting
confidence: 85%
See 1 more Smart Citation
“…I tested the hypothesis that syllid distribution related significantly to the abundance of dominant, habitat-forming macrobenthic species, such as the articulated coralline alga Amphiroa sp., which was dominant at 1.5 m depth. Unexpectedly, I found no significant relationship between this alga and syllid distribution, in contrast to observations elsewhere (Abbiati et al 1987, Serrano et al 2006. Geography and habitat dissimilarity might be at the base of the differences between the present study and that of Serrano et al (2006), who concluded that variation in abundance of habitat-forming taxa is one of the most important factors influencing the distribution of Syllidae along the Atlantic Iberian coast.…”
Section: Association With Dominant Macrobenthic Speciescontrasting
confidence: 85%
“…Syllid species composition, however, appears almost unrelated to algal cover, suggesting the absence of habitat-specific associations (Giangrande et al 2003). In general, it is suggested that the Syllidae should be abundant wherever a 3-dimensional substrate provides suitable microhabitats for settlement (Abbiati et al 1987, Giangrande 1988.…”
Section: Introductionmentioning
confidence: 99%
“…Syllids require spatial structures at microhabitat level not at macrohabitat level (Abbiati et al, 1987;Giangrande, 1988), this producing a high faunal homogeneity between habitats according to several workers (e.g. Cognetti, 1957;Giangrande, 1988;López and Viéitez, 1999;Tena et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Algal communities with their high structural complexity are important biotopes for zoobenthos, and the form of the pilot alga directly influences the macrobenthic community structure (Abbiati et al 1987;Giangrande 1988;Krapp-Schickel 1993;Chemello and Milazzo 2002;Fraschetti et al 2002;Antoniadou et al 2004). Polychaetes are among the most abundant taxa on hard bottoms, usually comprising over one-third of the richness both the species and the numerical abundance (Giangrande et al 2003;Chintiroglou et al 2004;Antoniadou et al 2004).…”
Section: Introductionmentioning
confidence: 99%